Socio spatial integration and dynamic in the metropolitan areas of Madrid and Copenhagen - Kristensen, G.; Rubio Benito, María Teresa; Rojo, T. (Espacio Tiempo y Forma. Serie VI, Geografía, 1992)
It is well known that towns tend to segregate socially, with lower interaction between different social groups, as a consequence. The role of the housing market is crucial in this procesa. The purpose of this paper is to discuss the social dynamics and the structuring capacity of housing over social interaction of groups, on the basis of comparative empírica! data, for the Madrid and Copenhagen metropolitan áreas.